2020
DOI: 10.4103/apjon.apjon_31_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Preoperative Anxiety Levels in Patients Undergoing Breast Cancer Surgery

Abstract: Objective: Patients' anxiety and stress levels are increased after the surgery. High levels of anxiety and stress could increase postoperative complications, as well as to prolong postoperative hospitalization and postoperative morbidity. This prospective, cross-sectional study was to evaluate the preoperative stress levels in patients undergoing breast cancer surgery. Methods: In the study participated 165 female patients who underwent breast cancer surgery, in a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Other postoperative studies support these results, as multiple studies report better HRQoL post-surgery in most or some domains for women receiving BCS [3,7,24,25]. Similar to our findings, studies that have looked at preoperative patients have shown that women scheduled to receive breast cancer treatment report poor sleep quality, symptoms of depression, anxiety, fatigue and pain [9,28,29]. Many women have described the newly diagnosed time period the most difficult and struggled with feeling of despair, hopelessness, and distress [30,31], however these studies focus on time of diagnosis, rather than the preoperative period.…”
Section: Discussionsupporting
confidence: 88%
“…Other postoperative studies support these results, as multiple studies report better HRQoL post-surgery in most or some domains for women receiving BCS [3,7,24,25]. Similar to our findings, studies that have looked at preoperative patients have shown that women scheduled to receive breast cancer treatment report poor sleep quality, symptoms of depression, anxiety, fatigue and pain [9,28,29]. Many women have described the newly diagnosed time period the most difficult and struggled with feeling of despair, hopelessness, and distress [30,31], however these studies focus on time of diagnosis, rather than the preoperative period.…”
Section: Discussionsupporting
confidence: 88%
“…This increase in the care dependency level paves the way for mental problems in patients (7,14). It was stated that one of the most prevalent mental problems observed in cancer patients was anxiety (5,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on breast cancer patients demonstrated moderate-to-severe anxiety in almost 50% of the patients. [ 15 ] Additionally, as modified PEC block is not associated with any nerve injury, we decided to perform it after general anaesthesia as it is more comfortable for patients.…”
Section: Discussionmentioning
confidence: 99%